The functions of memorable consumption experiences : Case Leijona brand - Turunen, Linda; Laaksonen, Pirjo (Kulutustutkimuksen seura, 2018)
Although consumers’ brand decisions are influenced by prior experiences via memory, the brand meanings stored in memories have received little attention in marketing and consumer behavior research. This study analyzes brand-related consumption experiences in order to find out what makes these experiences memorable for a consumer. The study was conducted by investigating brand memories from the point of view of the uses or functions of episodic memory. The empirical data consists of 1048 written stories about memorable consumption experiences related to a Finnish watch brand. The empirical data was explored through content analysis with deductive logic to uncover how memory functions (self-reflective, social and directive functions) come into existence in written stories. The findings revealed that the brand is tied to consumers’ life stories in multiple ways, and the meanings of the branded product were created particularly in socially, spatially and temporally specified consumption situations.
Keywords: fi=Markkinointi|en=Marketing|